Wushu e aspectos do treinamento: uma revisão da literatura - Hélio Mamoru Yoshida; Samuel Ribeiro dos Santos Neto (Universidade Estadual do Oeste do Paraná, 2016)
The aim of this study was to conduct a literature review on aspects of Wushu training toward competition. For this, a search was done between January 1996 and December 2016 of scientific articles. The following terms "Kung Fu Treinamento", "Wushu training", "Kung Fu periodização" e "Wushu periodization" were used in the BIREME, Scielo, Scopus, Science Direct, Pubmed and Lilacs databases. The following inclusion criteria were adopted: articles in English and Portuguese; Original studies; the subjects should have indicatives of participation in competitions. As exclusion criterion were: rehabilitation and health studies; studies involving only biomechanical analysis, unrelated to the training/competition processes; articles that did not approach the modality studied. In total, eleven studies were analyzed and divided between aspects of physical, technical, tactical and/or psychological training. Concerning the physical aspects, this study found that the Wushu Taolu and Sanda is predominantly anaerobic. To the psychological aspects, the cognition of young practitioners of Wushu showed no statistically significant differences in comparison with the control group. In addition, the mental toughness was emphasized to deal with adversity. In this literature review, no studies were found about the tactical and technical aspects to the mode of Wushu, focusing on the competition. Faced the difficulty to finding studies related to this thematic, we suggest the adoption of a proper nomenclature for Wushu and their submodalities. Despite the few studies found, we believe that this study is an important tool for future practical and/or the scientific studies focused training for competitions.